The formation of religious values in adolescence (Actual Problems of Psychology in Educational Institutions, 2019)
The article analyzes the problem of formation of religious(moral) values o f the personality in adolescence. The concept of religious valuesa s a basis for the moral principles of society is considered. Examples ofmethods for studying religious (moral) values a re given. The results ofdiagnostics of the level of formation of religious (moral) values a re presented.The difference between the results of the research between the tested groups ofadolescents is demonstrated. The influence of religious teaching on theformation of moral values in adolescence is described. The methods ofeducational influence on introduction of religious education are offered.
Keywords: r eligious values, moral values, adolescence, moral development of the individual, religious education